Pengaruh Disiplin Kerja Dan Kepribadian Karyawan Terhadap Kinerja Karyawan PT Charoen Pokphand Jaya Farm Pandeglang - Siti Faiza Azzahra; Didi Wandi; Yulaikah Yulaikah (INDO PUBLISHING, 2026)
This study aims to evaluate the extent to which work discipline and personality affect employee performance at PT Charoen Pokphand Jaya Farm Pandeglang. The background of the study shows an increase in employee absenteeism, which reflects a low level of discipline, while personality aspects are also considered an important factor in supporting performance. This study uses the theory of Organizational Behavior proposed by Stephan P. Robbins in 1996. This study uses a quantitative method involving the entire population consisting of 58 permanent employees in the Production Department, through a saturated sampling technique. Data collection was carried out through questionnaires, documentation, and interviews. Data analysis used the Partial Least Squares (PLS) method with the help of SmartPLS software version 4.0. The results of the analysis show that Work Discipline has a significant influence on employee performance. This is evidenced by the results of the t-statistic value of 3.255 and p-values of 0.001, which means the value is <0.5 with an original sample of 0.410. Employee Personality has a significant influence on employee performance. This is evidenced by the p-value of 0.004, which means the value is <0.5 with the original sample of 0.349. From these results, employee personality influences employee performance. Between the two variables, work discipline provides the greatest contribution to improving performance, and simultaneously work discipline and employee personality have a positive and significant effect on employee performance.